PENGARUH MEDIA PEMBELAJARAN ONLINE, MOTIVASI BELAJAR, DAN KOMPETENSI DOSEN TERHADAP KUALITAS PEMBELAJARAN - Ridaul Innayah (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The aim of this research are: 1) know the direct effect of e-learning/online learning media to quality of learning in economic education students at Unirow Tuban 2) know the direct effect of learning motivation to quality of learning in economic education students at Unirow Tuban, 3) know the direct effect of lecturer competence to quality of learning in economic education students at Unirow Tuban, 4) know the indirect effect of online learning media to quality of learning through learning motivation in economic education students at Unirow Tuban, and 5) know the indirect effect of lecturer competence to quality of learning through learning motivation in economic education students at Unirow Tuban. The sample of this research was part of the Economic Education students at Unirow Tuban in the even semester of the 2019/2020 academic year, amounting to 140. The data in this research were collected through a questionnaire and documentation, then analyzed using path analysis. The results showed that online learning media had a positive direct effect to quality of learning by 10%, and had an indirect positive effect on the quality of learning by 4,2%. Learning motivation had a positive direct effect on the quality of learning by 13.6%, Lecturer competence had a positive direct effect on the quality of learning by 73.7%, and had a positive indirect effect on the quality of learning through learning motivation by 8.4%.Keywords: Learning motivation, Lecturer competence, and Online learning media.